Effects of organic amendments on sand dune fixation - E. A. Elhadi; A. R. Mubarak; F. A. M. Rezig (International Journal of Recycling of Organic Waste in Agriculture)
Background Poor physical and chemical properties of sand dune soil are the main constrains in afforestation of sand dune in desertified area. The aim of this study is to improve the physical and chemical properties of dune soil in Elrawakeeb Dry Land Station using organic wastes as a fertilizer source and amendments, for sustainable sand dune stabilization program. Salvadora persica L. seedlings were transplanted in a 2 m 9 2 m plots and treated with: sawdust (SW), chicken manure (CH), chicken manure with sawdust (CH ? SW), sawdust with inorganic fertilizer (SW ? IF), sewage sludge (SS), sewage sludge with sawdust (SS ? SW), and control (C). The treatments were arranged in a randomized complete block design with four replicates. The soil chemical properties were determined from soil samples collected from the fixed sand dune (0â20 cm depth) in the second year after application. Results Application of organic amendments significantly (P = 0.001) increased soil organic carbon by 224 %, available P by 139.9 %, total nitrogen by 142.9 %, and mineral nitrogen by 83.5 % and decreased soil pH by 5.6 %. Conclusions Incorporation of organic waste in desertified sandy dune soils increased its nutrient content and hence sustained biological fixation of sand dunes.